BUNGA DAN RIBA - Muhammad Muhammad (Al Qalam, 2011)
Interest and riba' become interesting discourses frequently debated by Muslims scholars all the time. Some of them, for several reasons, view that interest is something different from riba'. This view is represented by Muslim scholars recognized as Islam modernists. Meanwhile, some others view both interest and riba' are similar; a unity which can not be distinguished and separated. According to this second group, interest is riba', and riba' is interest. This group is wellknown as Islam-Neo revivalists.This article does not intend to confrontate both of these two groups, Islam modernists and Islam-Neo revivalists. It just tries to explore the Islam-Neo revivalists' views on their main base in understanding the similarities between interest and riba', and their impacts in creating the stability of economy. Keywords: Neo-Revivalist, Interest, riba', fair, Economy, Islamic Banking